The effect of four weeks of resistance training with and without blood flow restriction on levels of anabolic and catabolic hormonal markers in middle-age sedentary males - Javad Vakili; Saeed Nikookheslat; Farid Pakzad Hassanlou (Journal of Sport & Exercise Physiology (JSEP) / Fīziyuluzhī-i Varzish va Fa̒āliyyat-i Badanī, 2022)
Purpose: Recently, the use of resistance training with restricted blood flow (BFR) has been recommended as an alternative to heavy resistance training for middle-aged and elderly people. Therefore, the aim of this research was to determine the effect of resistance training with and without BFR on levels of anabolic and catabolic hormones in middle-age sedentary male.Methods: In this semi-experimental study design, 20 voluntary middle-aged sedentary men (age 47.65 ± 2.53 years) were selected. Subjects were randomly divided into two groups of resistance training with and without BFR. Subjects in the 4-week BFR group performed knee extension and leg press at 20% 1-RM intensity, one set of 30 repetitions and two sets of 15 repetitions, and the non-BFR training group performed the same movements at 80% 1-RM intensity in three sets with 10 repetitions. Blood samples were also taken to measure testosterone and cortisol, growth hormone and insulin-like growth factor-1. Finally, Data were analyzed by analyses of variance and independent T test. The significance level was set at P < 0.05.Results: Resting concentrations of growth hormone (P = 0.001), IGF-I (P = 0.001), and serum testosterone (P = 0.001) response increased significantly after four weeks of resistance training. Also, the only increase in resting growth hormone was significantly higher in the BFR group (P = 0.04). However, four weeks of resistance training with (P = 0.11) and without Restricted blood flow (P = 0.55) did not significantly change cortisol concentration.Conclusion: It seems likely that performing resistance training with BFR during middle age is a good way to achieve the health benefits of exercise training due to hormonal adaptations.